Small-angle x-ray scattering study of polyelectrolyte solutions - Tomšič, Matija (Acta chimica slovenica, 2001)
Small-angle X-ray scattering (SAXS) technique has been used to study solutions of salts of poly(styrenesulphonic) acid containing lithium, strontium, and a mixture of lithium an strontium counterions. Repulsive electrostatic interactions between the polyions lead to a decrease of scattering, intensity at small values of the scattering vector q followed by a more or less pronounced interaction peak. The position of the maximun varies with polyion concentration and is strongly affected by the counterion charge. Addition of simple electrolyte to the solution causes an increase of the forward scattering; at sufficient concentration of added salt the peak vanishes and the behaviour of the system becomes similar to the solution of neutral polymer.
Keywords: interakcije; makroioni; polielektroliti; poliioni; polistirensulfonati; protiioni; raztopine; rentgenske metode